Intravenous Lidocaine Decreased the Median Effective Concentration of Sufentanil for Tracheal Intubation in Obese Patients - Jia D; Yuan X; He C; Tu F (Dove Medical Press, 2023)
Dong Jia, Xueying Yuan, Chaoqun He, Faping Tu Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of ChinaCorrespondence: Faping Tu, Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People's Republic of China, Tel +86-13808270833, Email tfpnc@163.comPurpose: Sufentanil has been widely used to inhibit the hemodynamic responses caused by tracheal intubation. Using intravenous lidocaine may reduce the dose of sufentanil and better maintain the hemodynamics. This study aimed to determine the effects of intravenous lidocaine on the median effective concentration (EC50) of sufentanil for endotracheal intubation in obese patients.Patients and Methods: This is a randomized, double-blind, up-and-down sequential allocation study. Fifty obese patients undergoing bariatric surgery were randomly allocated in a 1:1 ratio into the lidocaine group and the saline group. Anesthesia was induced using a target-controlled infusion of propofol and sufentanil. The effect-site concentration (Ce) of propofol was 3.5 μg/mL. The Ce of sufentanil for the first patient was 0.4 ng/mL, and the sufentanil dose for the next patient was determined according to the responses of the previous patient, using Dixon's up-and-down sequential method with an interval of 0.05 ng/mL. When the target concentration of propofol and sufentanil was reached, lidocaine 1.5 mg/kg or the same volume of normal saline was infused over 3 min. Tracheal intubation was performed 3 min after the end of the lidocaine or normal saline infusion. Probit regression was used to calculate the EC50 and 95% confidence interval (CI) of sufentanil.Results: Thirty-eight patients completed this study. The EC50 of sufentanil was 0.36 ng/mL (95% CI: 0.31- 0.41 ng/mL) in the lidocaine group, which was significantly lower than 0.50 ng/mL (95% CI: 0.43- 0.62 ng/mL) in the saline group. In addition, compared with saline group, the dosage of sufentanil in lidocaine group decreased significantly during the test. The hemodynamics of the two groups were stable during the study period.Conclusion: Intravenous lidocaine 1.5 mg/kg decreased the EC50 of sufentanil required for tracheal intubation in obese patients undergoing bariatric surgery.Keywords: lidocaine, median effective concentration, sufentanil, obesity